A Systematic Review on Randomized Controlled Trials Impact of Intestinal Anthelmintic Drug Administration on Hemoglobin Levels (Cuestiones de Fisioterapia, 2024)
Anemia is a major concern in the common health with extensive implications on human health, economic performance, and social progress. Although iron deficiency is generally recognized as the most common cause of anemia, the contribution of intestinal helminths to anemia has been getting an increasing interest. The objective of the present systematic review and meta-regression analysis is to assess the effect of regular intestinal anthelmintic drugs on the hemoglobin levels and the prevalence of anemia. The effect of deworming on baseline anemia, and the predictors of efficacy were studied by conducting a comprehensive search of randomized controlled trials. The meta-regression analysis showed that the effect of deworming on hemoglobin was significant but small particularly in high-prevalence anaemic populations. The adult populations showed the most significant improvement whereas the effect was not that significant in case children were included. Also, there was no significant difference in the effectiveness of iron supplementation used together with deworming to improve hemoglobin levels at the other factor held constant. The decrease in prevalence of anemia was highest at lower cut-offs of hemoglobin (e.g. 180 g/l) especially in high-baseline anemia populations. These results indicate that deworming may be a useful intervention particularly in those regions where anemia is severely high.